Effects of planting date and location on phenology, yield and yield components among selected cowpea varieties. - Shiringani, Rhandzu Patience. (My University, 2007)
Cowpea (Vigna unguiculata L. Walp) is one of the important food legumes and a valuable component of the traditional cropping systems. It serves as a source of protein in human diet and plays a major role in animal nutrition. The crop is adaptable to harsh environments including extreme temperatures and water limiting conditions. There is limited information available in cowpea with regards to cultivar selection and performance studies across ranges of environments in South Africa. The objectives of the present study were to 1) determine the influence of different planting dates and locations on phenology, yield and yield components of selected cowpea varieties and 2) determine the relationship of seed yield to environmental conditions such as rainfall and temperature. Ten cowpea genotypes were used for the study, developed by the Agricultural Research Council, Grain Crops Institute, South Africa. The experiment was laid out in a randomized complete block design with three replications. The experiment was carried out at Potchefstroom, Taung (Northwest Province) and Syferkuil (Limpopo Province) during three planting dates viz. 8 Nov. 22 Nov and 6 Dec. 2004. Data collected included the number of days to 50% flowering, number of days to 50% physiological maturity, seed yield, number of branches per plant, number of pods per plant, number of seeds per pod and 100 seed weight. The results showed highly significant differences among cowpea genotypes in each location and across locations for yield and yield components. Planting date one (i.e. 08 November) was better in yield gain over all locations. Potchefstroom was the best location for best yield gain due to high rainfall and relatively favorable low temperatures. The lowest yield was recorded at Syferkuil because of low rainfall and high temperatures. With relatively better performance across locations IT18E-16, CH14 and Pan311 were the best genotypes recommended in these or other similar environments in South Africa.
Thesis (M.Sc) (Agriculture)--University of Limpopo, 2007.
Keywords: Cowpea; Protein; Traditional cropping systems; South Africa